Estudo do fluxo de material fragmentado na mineração subterrânea, com o uso de modelos físicos - Jose Margarida da Silva (2005)
The main objective of this work was the study of gravity flow in excavations, mainly ore passes, in underground mining, by use of physical models. At review of literature it is presented terminology, flow properties of bulk materials, laws of gravity flow, flow design, flow patterns, flow phenomena, such as arching and rat holing, issues of security at work in ore pass systems, mining methods and materialtransfer systems and approaches about the study of gravity flow in ore passes. It was accomplished a rising of the practices on underground mines about gravity flow in excavations. This rising revealed the absence of data, methodology, adequate approach and adequate literature about this matter. It is necessary establishment of carefully and detailed records about evolved phenomena, according local conditions. From the developed work, it is presented physical properties of materials utilized attests in bins and pass models, and in inclined tubes. It is presented the equations determined from data. The results revealed the difficulty of rate of discharge prediction. It is presented physical model construction, at reduced scale. This model is based on ore pass in ore body mined by sublevel stoping. It is also recorded phenomena description, measured parameters, results of volumetric discharge rate. The design ofphysical model is detailed. These results are analyzed, conclusions are established and suggestions to new researches are presented.The results revealed the influence of ratio of pass section dimension to maximum particle dimension, moisture, presence of argillaceous materials and of the material column on gravity flow.